Factors associated with preterm birth in women undergoing cervical cerclage. (August 2020) - Kunpalin, Yada; Burul, Giorgia; Greenwold, Natalie; Tetteh, Amos; Casagrandi, Davide; Warner, Deborah; Fox, Georgina; Greig, Eliza; James, Catherine P; David, Anna L.
Abstract: Objectives: Cervical cerclage is used to manage women at high risk of late miscarriage (LM) and spontaneous preterm birth (PTB) due to factors such as history of cervical insufficiency (CI), uterine anomaly, cervical surgery and ultrasound (US) diagnosed cervical shortening. Urinary tract infection (UTI) and subsequent pyelonephritis, and bacterial infection are associated with PTB, but their role in PTB after cervical cerclage is unknown. We examined the relationship between UTI and bacterial vaginosis (BV), fetal fibronectin (fFN) test and PTB in women undergoing elective- or US-indicated cervical cerclage. We also investigated whether fetal fibronectin (fFN) test were useful to predict PTB. Study design: This is a single center, retrospective study of singleton pregnant women at PTB clinic, University College London Hospital (UCLH, 2005–2015) who underwent elective or US-indicated cervical cerclage. Women were tested for UTI and BV before cerclage placement and received mid-gestation fFN testing. Patient data were extracted from the PTB clinic database and electronic records. Statistical analyses used Pearson's chi-square and Mann-Whitney U tests. P values were corrected by Bonferroni method as required. Results: 267 singleton pregnant women attended our clinic with completed birth outcome. Of those, 32.2% (86/267) delivered prematurely. All women with UTI or BV received antibiotic treatment. Women with a UTI before cerclage placement were more likely to deliver preterm when compared to those with negative MSU culture (OR 3.39, 95%CI 1.24-9.27, p = 0.04). Their gestational age at delivery were also lower than those with negative MSU result (36 +6, IQR 31 +4 -38 +2 week vs 38 +1, IQR 36 +1 -39 +5 -week, p = 0.05). However, UTI after cerclage placement or BV either before or after cerclage placement were not associated with PTB. Women who had a positive fFN result were more likely to deliver preterm (OR 3.85, 95% CI 1.81–8.41, p = 0.0007). Conclusions: The presence of a UTI before cervical cerclage is associated with a higher rate of PTB in women who receive a cervical cerclage, even when treated. We did not find an association between pre or post-cerclage BV or post-cerclage UTI and PTB. Further research is needed to elucidate the link between UTI and PTB in women undergoing cervical cerclage.